Petrography, geochemistry and origin of atypical sedimentary-igneous contact relationships at the base of the Hotazel Formation around Middelplaats, Northern Cape Province, RSA - Terracin, Matthew Theodore (Rhodes University, Faculty of Science, Department of Geology, 2014)
In the Middelplaats mine area of the Kalahari manganese field, two drill holes (MP53 and MP54) intersected anomalously high-grade manganese ore sitting stratigraphically just above an igneous body (likely a dike or sill). Manganese ore located within approximate 5 meters of the contact with the underlying igneous rocks has been substantially metasomatically upgraded from 25 percent manganese, to over 40 percent whilst the dominant manganese species within the ore has been altered to hausmannite. This report demonstrates the metasomatic alteration is related to devolatilization (removal and/or remobilization of Hâ‚‚O, COâ‚‚ and CaO) due to contact metamorphism caused by the underlying igneous rocks. The Middelplaats mine is situated in the southwest corner of the Kalahari manganese field where the paleo basin shallows out and ends. Within the mine area, several stratigraphic units pinch out or are truncated by the side of the basin. This pinching out of lithological formations has led to the underlying Ongeluk Formation being in contact with the much younger units of the Hotazel Formation. Therefore, geochemical investigation into the nature and source of the igneous rocks was also undertaken to see if the rocks from the two drill holes were related to one another and/or the underlying Ongeluk Formation. Results of these geochemical studies have demonstrated that the Middelplaats igneous rocks (dolerites) from the two drill holes (MP53 and MP54) share a co-genetic source region. There is also reasonable geochemical evidence that the source region of the Middelplaats igneous rocks was substantially similar to the source region of the Ongeluk Formation. This may indicate that the source region of the Ongeluk Formation was reactivated at some later stage resulting in the emplacement of doleritic dikes or sills in the Middelplaats mine area. The Middelplaats igneous rocks were also found to have undergone a slight but pervasive potassic alteration; with most of the original plagioclase feldspar showing some level of replacement by a potassium enriched feldspar. Although no source for this potassic fluid was found, the devolatilization reaction within the manganese ore appears to have released some potassium into the surrounding rocks. This additional potassium may be responsible for some localized potassic alteration.
Keywords: Petrology -- South Africa; Geochemistry -- South Africa; Igneous rocks -- South Africa; Manganese ores -- South Africa; Manganese ores -- Geology -- South Africa; Metasomatism (Mineralogy); Potassium